Silicon Anodization as a Structuring Technique Literature Review, Modeling and Experiments - Ivanov, Alexey; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2018)
Alexey Ivanov investigates the application of a silicon anodization process as a three-dimensional structuring technique, where silicon is transformed into porous silicon as a sacrificial layer or directly dissolved in electropolishing regime. The work contains a detailed state of the art, experimental studies and modeling of the process for basic shape controlling techniques. Limitations of the developed FEM model with secondary current distribution are discussed. Contents Silicon Anodization: State of the Art Experimental, Characterization and Simulation Methods Microscale Study of Anodization Process Anodization Process as a Structuring Technique: Experiments and Simulation Target Groups Researchers and students of microsystems technology, electrochemistry, microengineering Practitioners in the area of microsystems, silicon processing and electrochemical material processing <The Author Alexey Ivanov is currently working  as a research scientist at the Fraunhofer Institute for Solar Energy Systems (Fraunhofer ISE, Germany) on developing and optimizing anodization processes for large-scale fabrication of semiconductor photovoltaic cells and batteries.
Silicon Anodization: State of the Art -- Experimental, Characterization and Simulation Methods -- Microscale Study of Anodization Process -- Anodization Process as a Structuring Technique: Experiments and Simulation.
Keywords: Microtechnology; Microelectromechanical systems; Engineering mathematics; Engineering -- Data processing; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Microsystems and MEMS; Mathematical and Computational Engineering Applications; Engineering Thermodynamics, Heat and Mass Transfer